2018
DOI: 10.1002/ajh.25267
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and karyotype predict treatment response in myelodysplastic syndromes

Abstract: We examined the influence of mutations and karyotype on conventional treatment response, specifically hematological improvement in anemia, in primary myelodysplastic syndromes (MDS). Cytogenetic and next generation sequencing (NGS)-derived mutation information was available in 357 patients (median age 74 years; 70% males); the revised international prognostic scoring system risk distribution was very high in 11%, high 15%, intermediate 17%, low 40% and very low 16%. At least one mutation was detected in 81% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although earlier studies reported a favorable effect of TET2 mutations on response rates, 102,103 this association was not confirmed in a different cohort. 104 Finding predictive biomarker(s) for response to therapy is of particular relevance for the elderly population, which often displays lower response and higher toxicity rates. However, finding a magic "fits all" predictive biomarker in MDS is an unlikely scenario, considering the complexity of the disease and the role of several genetic, immunologic, and environmental factors in its pathophysiology.…”
Section: Clinical Experience With Immune Interventionsmentioning
confidence: 99%
“…Although earlier studies reported a favorable effect of TET2 mutations on response rates, 102,103 this association was not confirmed in a different cohort. 104 Finding predictive biomarker(s) for response to therapy is of particular relevance for the elderly population, which often displays lower response and higher toxicity rates. However, finding a magic "fits all" predictive biomarker in MDS is an unlikely scenario, considering the complexity of the disease and the role of several genetic, immunologic, and environmental factors in its pathophysiology.…”
Section: Clinical Experience With Immune Interventionsmentioning
confidence: 99%
“…63 In contrast, the higher response rate to azacitidine reported in patients carrying TET2 mutations 64 has not been consistently confirmed. 62,65 Novel treatment approaches…”
Section: Hmasmentioning
confidence: 99%
“…Mutated TET2 showed a higher response rate to azacitidine in MDS and low blast count AMLs 66 . TET2 mutations occurred in early disease evolution in MDS 62 , 67 , 68 . TET2 mutations were also found in T cell lymphomas 69 , 70 and diffuse large B‐cell lymphoma 71 , 72 .…”
Section: Frequent Mutations Of Tet2 In Other Tumorsmentioning
confidence: 98%